2015
DOI: 10.1080/09585192.2015.1079230
|View full text |Cite
|
Sign up to set email alerts
|

In the age of ‘liquid modernity’: self-initiated expatriates in Crete, their multi-generational families and the community

Abstract: In this paper, we aim to broaden and deepen the current debate on expatriation in business and management discourse, and especially self-initiated expatriation. Following Bauman's [Liquid Modernity (2000), Cambridge: Polity; Liquid Love, On the Frailty of Human Bonds (2003), Cambridge: Polity] critique of postmodern society and, employing an anthropological lens, we examine work-related expatriation as set within a wider life context. Whereas conventional expatriation research focus is on the workplace, the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Recently, Clark et al . () have explained how organizational and supervisor life‐domain support might mitigate the amount of resource drain felt by employees (loss spiral); for example, an employer who allows employees to work flexible hours may reduce the time demands attributable to life‐domain schedules, or a supervisor can help employees cope with their life‐domain demands in providing emotional (e.g., serving as a sounding board) or instrumental (e.g., offering suggestions for assistance) support. Some authors have also illustrated the gain spiral effect of organizational life‐domain support as a source of development and affective and capital gains.…”
Section: Literature Reviewsupporting
confidence: 83%
See 1 more Smart Citation
“…Recently, Clark et al . () have explained how organizational and supervisor life‐domain support might mitigate the amount of resource drain felt by employees (loss spiral); for example, an employer who allows employees to work flexible hours may reduce the time demands attributable to life‐domain schedules, or a supervisor can help employees cope with their life‐domain demands in providing emotional (e.g., serving as a sounding board) or instrumental (e.g., offering suggestions for assistance) support. Some authors have also illustrated the gain spiral effect of organizational life‐domain support as a source of development and affective and capital gains.…”
Section: Literature Reviewsupporting
confidence: 83%
“…Likewise, researchers should investigate the gender differences between IMEs, since domestic research has shown that employees may be influenced differently by gender roles, cultural norms, social power, etc. (Clark et al ., ; Ballesteros‐Leiva et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent business travelers referred to themselves as a group of ‘road warriors’, showing how cosmopolitan identities are ‘accomplished in the context of shared social spaces and conditions’ (Skovgaard‐Smith & Poulfelt, 2018, p. 131), but not, as in the case of the Amsterdam expatriates in their study, in fixed physical locations. Participants described accessing ‘social enclaves’ (Clark & Altman, 2015, p. 735) to create a new sense of belonging by identifying themselves as ‘non‐nationals’ (Skovgaard‐Smith & Poulfelt, 2018). Others sought but failed to establish networks, especially the families of those on corporate assignments.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Indeed, the growth of communication technology has enabled the development of networks ‘despite distance and the passage of time’ (Baldassar, 2016, p. 159). The significance of social networks on the ‘identity building’ of those engaged in expatriation is emphasized by Clark and Altman (2015, p. 735) who argue that expatriates tend to form ‘social enclaves in order to facilitate a sense of “home”’. This may be achieved through transnational social spaces, such as joining expatriate clubs, attending churches, meeting in cafes, engaging in web‐based chat forums and organizations that transcend national boundaries (Leonard, 2010).…”
Section: Social Networkingmentioning
confidence: 99%
“…In fact, migration is no longer the finite mobility transition it used to be. Migrants do not normally cut themselves off from their relations, friends and networks back home; their COI citizenship allows for the possibility to repatriate with changing economic, political or personal circumstances (Clark & Altman, 2015). Within political-economic blocks such as the contemporary EU, or the historical Habsburg Empire, migration and expatriation are conflated terms.…”
Section: What's In a Name? The Evolution Of The Expatriate Conceptmentioning
confidence: 99%